Inflation and economic development : progress report by the secretary-general - United Nations Economic and social council (1965)
This book is a progress report that the general assembly asked the secretary-general to prepare a study of inflation in the developing countries, clarifying the interrelationships involved and exploring the various lines of approach required to deal effectively with.
Thirty-ninth session agenda item 9
Includes bibliographical references
hza 28/01/2019
Loans